Implementasi mengaji ba'da maghrib dalam meningkatkan bacaan Al-Qur'an Anak Studi Kasus : Desa Ketanonageng, Sragi, Pekalongan - Reza Hidayat; Pujiyanto, Mohammad Nur Kholis (ABIDUMASY, 2025)
In Ketanonageng Village, Sragi District, the activity of reciting the Maghrib Koran has become part of the community's tradition. This activity, which is usually participated in by children, aims to introduce them more closely to the Koran and Islamic values, as well as strengthen their devotion from an early age. The iqro' method is the method used in Koran recitation activities in Ketanonageng Village, Sragi District. The aim of this research is to find out how the Maghrib Koran recitation activity is implemented in Ketanonageng Village, Sragi District, Pekalongan Regency, and to find out the level of success that has been achieved in this activity. Keywords​: ​​ Tradition, Koran Recitation Activities, Iqro' Method